Genotypic determination coefficient and genetic diversity at topcrosses between food type and grain type soybean - Yokomizo, Gilberto Ken-Iti; Vello, Natal Antonio (Pesquisa Agropecuaria Brasileira, 2000)
The estimates of the heritability coefficient are necessary for the choice of an efficient strategy of selection. When the treatments are considered fixed, the heritability is called genotypic determination coefficient. In the present work the genotypic determination coefficient and the genetic diversity to distinguish the differences between genetic contribution of exotic parentals from type food soybean with great seeds and small seeds in topcrosses with two adopted type grain parentals and the interactions with the environment were studied. The results of genotypic determination for the topcross averages was 90.51% for number of days for maturity (NDM); 93.92% for height of the plant at maturity (APM); 79.52% for lodging (AC); 91.37% for agronomic value (VA); 95.55% for one hundred seed weight (PCS); 57.57% for seed yield (PG) and 91.18% for pod width by visual score (LVV), that agree with the values found in literature. In relation to the estimates of genetic diversity, that represent the availability of genetic differences for selection, the characters NDM, APM and AC, showed higher values in the small seed of exotic parental topcrosses and for VA, PCS, PG and LVV in the great seeds of exotic parental topcrosses.
Keywords: Glycine max; progeny; selection; genetic variation; breeding methods